Epic interactions : perspectives on Homer, Virgil, and the epic tradition : presented to Jasper Griffin by former pupils - Clarke, Michael (Michael J.); Currie, Bruno; Lyne, R. O. A. M. (Oxford University Press, 2006)
This collection of chapters, written by former pupils of his, celebrates the career of Jasper Griffin, one of the foremost modern scholars of classical epic. The book surveys the epic tradition from the 8th century BC to the 19th century AD. Individual chapters focus on: Homer and the oral epic tradition; Homer in his religious context; Herodotus and Homer; Hellenistic epic; Virgil in his literary context; Virgil in his political-cultural context; the Augustan poets and the Aeneid; Statius' Thebaid; Old English and Old Irish epic; Renaissance epic: Tasso and Milton; and the Victorians. The aim of the book is to situate writers of epic in their literary and cultural contexts — the essence of the term ‘interaction’ in the title. The chapters singly offer insights into some of the foundational poems of the European epic tradition and together take a bold, holistic look at that tradition.